Non valvular atrial fibrillation stroke risk stratification by CHA2DS2-VASc score and short term outcomes - Pandharipande, Madhuri Sunil; Shinde, Shivraj V.; Motlag, Mrinalini Dinkar; Nagpure, Keshav; Joshi, Rakhi W.; Joshi, Prashant P. (International Journal of Research in Medical Sciences, 2017)
Background: Atrial fibrillation confers a high risk of stroke and is associated with significant mortality and morbidity. Many scoring systems for have been proposed stroke risk stratification in atrial fibrillation. Peripheral thromboembolism, heart failure and death. The main objective of the study was to estimate CHA2DS2VASc score in cases of non valvular atrial fibrillation, to asses short term outcome in AF (stroke, thromboembolism, heart failure and death and to find out association of CHA2DS2VASc score with outcomes. Methods: 64 cases (29 M, 35 F) of non valvular AF were included in this prospective observational study.CHA2DS2VASc score was calculated and cases were categorized into low (score 0), intermediate (score 1 ) and high risk (score 2 ) for development of stroke. Cases were clinically evaluated and investigated for type, etiology, complications and comorbidities. Results: CHA2DS2VASc score was determined in 64 cases of non valvular AF. In 3 cases (4.6%) it was zero indicating low risk for stroke, 8 cases (12.5%) had CHA2DS2VASc score as 1had intermediate risk, and 53 cases (82.8%) had score 2 or more indicating high stroke risk (p<0.01). 3 cases of non valvular atrial fibrillation (4.6%) presented with stroke and all of them had CHA2DS2VASc score>2. At the end of 3 months, total no. of cases with stroke was reported to be 5 (7.8 %). Stroke risk was significantly higher in cases of CHA2DS2VASc score>2 (p<0.01). Congestive heart failure was reported in 32 (50%) cases. Peripheral embolism was documented in 1 case (1.5%). Overall Mortality at the end of 3 months was reported to be 7 (10.9%) and cases with CHA2DS2VASc score ≥2 had 13% mortality. CHA2DS2VASc score ≥2 was significantly associated with mortality (p<0.01). All 3 Cases with CHA2DS2VASc score as zero were uncomplicated. 8 cases (12.5%) had score as 1 and, out of these 8 cases, CHF was reported in 2 cases (25%), while 6 (75%) were uncomplicated.CHA2DS2VASc score ≥2 was reported in 53 cases (82.3%). This group had complications in the form of CHF in 30 cases (56.6 %), thromboembolism in 1 (1.8%), and stroke in 5 (9.4%) cases. Cases of AF with CHA2DS2VASc score >2 demonstrated significantly high incidence for stroke as compared to those with score as zero or one (p<0.01). Conclusions: CHA2DS2VASc is a simple score to predict stroke risk in cases of non valvular atrial fibrillation and is easy to estimate. CHA2DS2VASc score ≥2; is associated with high incidence of stroke in cases of non valvular AF. CHA2DS2VASc score≥2 is associated with mortality as a short term adverse outcome in non valvular atrial fibrillation.